2017
DOI: 10.1007/s10147-017-1097-y
|View full text |Cite
|
Sign up to set email alerts
|

Current Status of Uterine Leiomyosarcoma in the Tohoku Region: Results of the Tohoku Translational Center Development Network Survey

Abstract: Although ULMS was associated with a high rate of complete or optimal surgery, the long-term prognosis was poor. Effective postoperative therapy should be developed to improve the long-term prognosis of patients with ULMS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…However, systemic staging surgery with an oophorectomy and LND is controversial in stage I uLMS (8). There is a consensus that ovaries should be removed in postmenopausal women (21). Most studies have found that ovarian preservation is safe in stage I premenopausal women, who have similar relapse and survival rates to women who undergo BSO (22).…”
Section: Second-look Surgerymentioning
confidence: 99%
“…However, systemic staging surgery with an oophorectomy and LND is controversial in stage I uLMS (8). There is a consensus that ovaries should be removed in postmenopausal women (21). Most studies have found that ovarian preservation is safe in stage I premenopausal women, who have similar relapse and survival rates to women who undergo BSO (22).…”
Section: Second-look Surgerymentioning
confidence: 99%